SPRING HYPOVITAMINOSIS IN CHILDREN - A.A. Ruleva (Вопросы современной педиатрии, 2011)
The prevalence of vitamins deficiency is widespread in the present times. Deficiency of vitamins is usual even in healthy growing child. It is largely presented in children with different diseases. The lack of sun, the air polluted with gases and worsening of nutrition quality aggravates the risk of hypovitaminosis development especially in winter and spring. The lack or absence of vitamins in diet leads to metabolic disorders, decrease of physical and mental activity and easy fatigability of organism. Reliable source of vitamins and minerals are polyvitamin drugs and vitamin-mineral complexes for prophylactic use. While treating with vitamins, the daily need, compatibility and balance of vitamin-mineral complexes should be taken into account.Key words: children, vitamins, deficiency.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (2): 155–161)